Southern Criminologies, Indigenous Stories and Qualitative Research. Issue 2 (18th July 2022) - Warren, Ian; Ryan, Emma
Abstract: Southern Criminologies offer an important site for representing Indigenous voices that can promote viable anti-colonial, reformist and abolitionist goals. This is crucial as Indigenous people and many other subaltern groups are commonly the objects of criminal justice research, rather than equal collaborators in the research process. This paper views Southern Criminologies as positive sites for incorporating traditional and emerging forms of Indigenous storytelling to supplement, rather than contradict, claims for the decolonization of criminology. We examine this argument in respect of two long-standing criminological developments. The first is a robust critical epistemology that challenges positivist assumptions about knowledge-building by overturning established racial, class, gendered and related power relations to reimagine how justice can be conceived. The second is the profound absence of qualitative forms of storytelling, and Indigenous storytelling specifically, that are credited for documenting the harmful links between law and order, justice administration, control, surveillance and the persistent lack of accountability for harmful conduct in criminological theory, methods and curricula. We suggest Southern Criminology can accommodate intellectual criticism by using stories to reimagine otherwise unchallenged facts about justice and surveillance in colonized societies, while offering a critical theoretical and applied bridge to connect Indigenous and non-Indigenous knowledges. This project requires attentiveness to the lived and imagined experiences of justice in Indigenous societies since colonization, and informed critiques of Northern metropolitan epistemologies that have contributed to attempted genocide and ongoing forms of coloniality through the institutional suppression of subaltern voices in Australia and other settler-colonial societies.